2009
DOI: 10.1177/0969733008097994
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to End-of-Life Decisions in Paediatric Intensive Care

Abstract: Key words: attitudes of health personnel; clinical ethics; end-of-life care; paediatric intensive care; treatment futilityThe aim of this study was to assess attitudes of intensive care nurses to selected ethical issues related to end-of-life decisions in paediatric intensive care units. A self-administered questionnaire was distributed in 2005 to intensive care nurses at two different scientific occasions in Turkey. Of the 155 intensive care nurse participants, 98% were women. Fiftythree percent of these had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…Although withdrawing treatment was often felt to be reprehensible, professionals also admitted it to be part of their job. In one study, for example, 40% of the Turkish intensive-care nurses justified withdrawing treatment when there was no medical benefit [27], and another study [75] found that 40% of the intensive-care physicians had discontinued treatment in patients with an incurable disease on more than one occasion. Withdrawing treatment was more difficult than not initiating the treatment [40], and was often a matter for discussion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although withdrawing treatment was often felt to be reprehensible, professionals also admitted it to be part of their job. In one study, for example, 40% of the Turkish intensive-care nurses justified withdrawing treatment when there was no medical benefit [27], and another study [75] found that 40% of the intensive-care physicians had discontinued treatment in patients with an incurable disease on more than one occasion. Withdrawing treatment was more difficult than not initiating the treatment [40], and was often a matter for discussion.…”
Section: Resultsmentioning
confidence: 99%
“…In one study 75% of health staff disagreed with the statement that, nutrition should be stopped if a patient wants euthanasia [58], while 68% of the nurses in another study agreed that artificial nutrition should always be continued [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Despite the expectation for nurses to contribute significantly to the decision‐making process in EOL care, existing research reveals that nurses' actual involvement in the decision‐making process is far below the expected level (Kennard et al , ; Akpınar, ; Yaguchi et al , ; Akpinar et al , ; Langley et al , ). A study conducted in Turkey demonstrated that nurses lack sufficient knowledge and skills in ethical decision making (Ersoy and Göz, ).…”
Section: Introductionmentioning
confidence: 99%
“…34 This result could also be interpreted as nurses being reluctant to stop treatment, as generally noted in health care professionals. 30,35 The tendency of more than half of the intensive care nurses not to discharge the patient with brain death, whose parents intended to donate his organs, was interesting because they preferred to save prospective patients' lives. This result also suggested that the nurses applied the Regulation on Organ and Tissue Donation, which states that 'medical support can only be discontinued if relatives of the patient approve it after brain death of the patient is declared to them'.…”
Section: Discussionmentioning
confidence: 99%